Group portrait of the attendees of the 1962 Monte Toyon Methodist Camp - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the Monte Toyon Methodist Camp, held August 25 to September 1, 1962, in Aptos, California.